Tempat Sampah Otomatis Menggunakan Sesnsor Ultrasonik Berbasis Arduino Uno - Iwang Rivaldi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The importance of innovation in waste management is increasingly felt in this modern era. This research introduces an automated waste handling system utilizing Arduino Uno-based sensors. Arduino Uno, as a versatile microcontroller, is employed to control the automation process in waste bins. Integrated ultrasonic and load cell sensors assist in identifying the presence of individuals disposing of trash and monitoring the weight of the waste, triggering the automatic disposal mechanism. This implementation not only enhances the efficiency of waste management but also provides convenience for sanitation workers. The study details the design, implementation, and performance evaluation of the automated waste bin system, showcasing the potential utilization of Arduino Uno technology in creating intelligent and sustainable solutions for waste management.